PENGARUH PEMBERIAN BERBAGAI KONSENTRASI ZPT 2,4-D (2,4-DICHLOROPHENOXYACETIC ACID) DAN BAP TERHADAP EKSPLAN DAUN DUKU KUMPEH SECARA IN VITRO - Tobing, Daniel Trisantoso Lumban; Lizawati, Lizawati; Jasminarni, Jasminarni (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2026)
The duku plant (Lansium domesticum Corr.) is a horticultural commodity originating from Southeast Asia. Duku Kumpeh is a national leading variety from Jambi Province which is seriously threatened due to the increasingly widespread attack of stem cancer. Tissue culture is an effort made to make plant parts (roots, shoots, other plant tissues) grow intact (perfect) in aseptic conditions. The research was carried out at the Biotechnology and Plant Breeding Laboratory, Faculty of Agriculture, University of Jambi. The research was carried out for 3 months from February to April 2026. This study employed a factorial randomised block design (RBD) comprising two factors: the first factor was the concentration of 2,4-D (0; 0.25; 0.5; 0.75; and 1 ppm) and the second factor was the concentration of BAP (0 and 1 ppm). A total of 10 treatments were obtained and replicated three times based on leaf groups or sections (base, middle and tip of the leaf), resulting in 30 experimental units. Each experimental unit consisted of 4 bottles, including 2 sample bottles, resulting in a total of 120 bottles, each containing a single leaf explant. The explants were cultured for 8 weeks after inoculation (MSK). The results of the study indicate that there is no interaction between the concentrations of the plant growth regulators 2,4-D and BAP and the variables of callus formation time and the percentage of callus-forming explants in Duku Kumpeh leaf explants. The application of various concentrations of 2,4-D alone was able to induce callus formation in Duku Kumpeh leaf explants, but BAP alone was not yet able to induce callus formation in Duku Kumpeh leaf explants. The application of 2,4-D at concentrations ranging from 0.25 to 1 ppm, combined with a BAP concentration of 1 ppm, is crucial for callus formation on Duku Kumpeh leaf explants.